ANALISIS AGROINDUSTRI KRIPIK UBI KAYU DI KELURAHAN KULIM KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Niken Nurwati; Rini Nizar; Amalia Amalia (Universitas Lancang Kuning, 2017)
The agricultural sector is the main pillar of economic development in Indonesia because Indonesia almost all economic activities centered on the sector. Processing of agricultural or agro-industry is the agricultural product processing business for the purpose of increasing the value of the product. Pekanbaru city produces one of the agricultural products that manioc. The highest production of cassava in Sub Tenayan Raya in Pekanbaru, namely 11 210 tonnes (Pekanbaru in number 2015). In connection with this condition, this study aims to analyze costs and revenues, Break Even Point (BEP), profit planning as well as the added value generated by the agro-industry critic's capable of cassava in Kulim Tenayan Raya Pekanbaru. It can be concluded:1.The cost of agro-industrial production processes cassava chips